2022
DOI: 10.3389/fpls.2022.854716
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiling and Transcriptome Analysis Unveil the Mechanisms of Red-Heart Chinese Fir [Cunninghamia lanceolata (Lamb.) Hook] Heartwood Coloration

Abstract: Red-heart Chinese fir (Cunninghamia lanceolata) has the advantages of high density and attractive color, making it popular in the market. To date, most studies about stems of woody plants have only been reported at the cytological level because of few living cells. In this study, the xylem was successfully partitioned into three effective sampling areas: sapwood, transition zone, and heartwood. Secondary metabolites, cell survival, and differentially expressed genes in the three sampling areas were, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Compared with WH, RH has more upstream substrates and downstream glycosylation products, which ultimately changes the color of heartwood. In a previous study, we found that the differentially expressed genes in phenylalanine pathway (PAL, C4H, and 4CL), upstream of flavonoid biosynthesis pathway (CHS, CHI and F3H) and glycosylation (UGT) were all up-regulated in the transition zone of RH compare to WH ( Cao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Compared with WH, RH has more upstream substrates and downstream glycosylation products, which ultimately changes the color of heartwood. In a previous study, we found that the differentially expressed genes in phenylalanine pathway (PAL, C4H, and 4CL), upstream of flavonoid biosynthesis pathway (CHS, CHI and F3H) and glycosylation (UGT) were all up-regulated in the transition zone of RH compare to WH ( Cao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 88%
“…In a previous study, we found that the differentially expressed genes in phenylalanine pathway (PAL, C4H, and 4CL), upstream of flavonoid biosynthesis pathway (CHS, CHI and F3H) and glycosylation (UGT) were all up-regulated in the transition zone of RH compare to WH (Cao et al, 2022). By analyzing the 12 phenotypic traits of the 300 core populations screened, it was shown that the traits of this population were little affected by the environment and can be inherited stably (Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations